Toxicity Index, Patient-Reported Outcomes, and Early Discontinuation of Endocrine Therapy for Breast Cancer Risk Reduction in NRG Oncology/NSABP B-35. Issue 34 (1st December 2021) - Henry, N. Lynn; Kim, Sungjin; Hays, Ron D.; Diniz, Marcio A.; Luu, Michael; Cecchini, Reena S.; Yothers, Greg; Rogatko, André; Ganz, Patricia A.
Abstract : PURPOSE: The US National Cancer Institute Moonshot initiative calls for improving analysis and reporting of toxicity to inform treatment tolerability. We used existing clinician-reported adverse event (AE) and patient-reported outcome (PRO) questionnaire data from the randomized, double-blind NSABP B-35 clinical trial to explore reasons for anastrozole and tamoxifen discontinuation. METHODS: Postmenopausal women with ductal carcinoma in situ treated with breast-conserving therapy were randomly assigned to anastrozole or tamoxifen for 5 years. The primary outcome for this analysis was time to treatment discontinuation. AEs were collected every 6 months post–random assignment from all 3, 104 participants and summarized using the Toxicity Index (TI). PRO data were collected at baseline and every 6 months from 1, 194 participants. Univariate and multivariable analyses of time to treatment discontinuation were performed using Cox regression models with TIs and PROs as time-dependent covariates. RESULTS: Of 3, 046 analyzed participants, 869 (28.5%) discontinued treatment prematurely. In multivariable analysis, when both baseline PROs and on-treatment AEs were considered, thrombosis and arthralgia AEs were associated with discontinuation of both tamoxifen and anastrozole; additional AEs associated with discontinuation varied by drug. In addition, baseline pain interference, hot flashes, and unhappiness were associated with tamoxifen discontinuation (n = 589; overall Harrell's C-statistic 0.686 [95% CI, 0.640 to 0.732]); no baseline PROs were associated with anastrozole discontinuation (n = 589; overall Harrell's C-statistic 0.656 [95% CI, 0.630 to 0.681]). When only baseline PROs were examined, pain interference, hot flashes, and unhappiness were associated with shorter time to discontinuation of tamoxifen; only hot flashes were associated with discontinuation of anastrozole. CONCLUSION: Analysis of AEs using the TI yielded important insights into reasons for discontinuation of endocrine therapy that was enhanced by the addition of PRO baseline and treatment-emergent symptoms. Abstract :